Dental Student Perceptions of Distance Education over Time: A Mixed-Methods Study - Susanna Y. Yeh; Nithya Puttige Ramesh; Kristie Kaczmarek-Stewart; Chiho Ahn; Alice Z. Li; Hiroe Ohyama (MDPI AG, 2023)
Objectives: Amid the COVID-19 pandemic, the transition to distance learning raised pertinent questions regarding advantages and challenges compared to traditional in-person learning. This study aimed to investigate dental students' perceptions of distance learning throughout the pandemic, examining its impact on their education. Methods: This study employed a convergent mixed-methods design. Three online surveys were conducted in 2020, 2021, and 2022 to collect quantitative data. Additionally, qualitative semi-structured interviews were carried out in 2022. Interviews were recorded and transcribed; then, thematic analysis was performed following an inductive approach. Results: As perceived by the participants, distance learning entails advantages and challenges. Initially, they felt uncertainty and negativity about the new environment with distance learning. However, their perceptions shifted positively as they adapted, even after returning to hybrid and in-person modules. Furthermore, most participants felt that distance learning is better suited for didactic content. It was suggested that didactic courses contain approximately 25-50% of online methods. Conclusions: Distance learning has provided valuable opportunities to reinforce curricula and improve learning efficacy during the pandemic. Our findings suggest that a hybrid learning model that combines traditional and distance modules appears to be an effective approach for future dental education.